What factors promote or hinder women with diabetes accessing preconception services? - Hughes, Chantelle (2014)
Abstract Background Diabetes is the number one long-term condition that complicates pregnancy. It significantly increases the risk of infant mortality and congenital abnormalities. Key to reducing this risk is the planning of pregnancy, yet up to fifty percent of women with diabetes (WWD) are having unplanned pregnancies. Aim To identify what factors influence WWD in accessing pre-pregnancy services. Method A critical review was performed, accessing a variety of health and social science sources. Findings The review identified a number of themes that influence whether WWD access pre-pregnancy services. These include:  Not relating to the concept of a planned pregnancy,  Poor socio-economic circumstances,  Desire for a ‘normal pregnancy’ ,  Belief that services are not aimed at them, and  How diabetes services are provided, including excessive appointments, lack of patient-centeredness, and inadequate healthcare professional knowledge. Discussion This review identifies that to encourage WWD to access pre-pregnancy services healthcare professionals need training to improve knowledge and interpersonal skills. An effective way of doing this is through involving service users in education. Professionals also need to be aware of the language they use, to ensure that services are approachable to WWD. Additionally, healthcare providers should promote the notions of a ‘normal pregnancy’ within services. Furthermore, with the high level of commitment diabetes management requires, there are other approaches to information provision that could be used, including the production of books, DVDs, CD-ROMs and internet resources. Alternatively, appointments may be condensed using interprofessional clinics. viii Conclusion This review identifies a number of ways in which service provision may be improved to increase uptake of pre-pregnancy services and health outcomes for WWD. Though, further research is required to establish the efficacy of these recommendations specifically with this population.